Contemporary perspectives on early childhood education - Yelland, Nicola, 1952- (McGraw-Hill/Open University Press, 2010)
This book considers and interrogates a range of new and critical issues in contemporary early childhood education. It discusses both fundamental and emerging topics in the field, and presents them in the context of reflective and contemporary frameworks.